Affinity selection mass spectrometry (AS-MS) for prospecting ligands in natural product libraries - do Amaral, Bruno S.; de Moraes, Marcela C.; Cardoso, Carmen L.; Cass, Quezia B. (Frontiers in Natural Products, 2025)
Natural product libraries are a source of diverse 3D molecular features furnishing an array of biological functions in drug discovery research. In this paper we will oversee the use of affinity selection mass spectrometry (AS-MS) for identifying ligands to a variety of biological targets using natural products as the molecular library. The assay modes used in solution or with the immobilized target and their pros and cons will be presented. Additionally, the required experiments and investigation for accurate chemical annotation of the disclosed ligands in a non-target assay are discussed.